Pengaruh Latihan Bola Gantung Terhadap Kemampuan Servis Atas Bola Voli Putri Ekstrakurikuler SMPN 2 Kota Bengkulu: The Effect of the Hanging Ball Training Model on Extracurricular Female Volleyball Service Ability at SMPN 2 Bengkulu City - Putra Pratama; Tono Sugihartono; Deliyanto (SPORT GYMNASTICS : Jurnal Ilmiah Pendidikan Jasmani, 2023)
Abstract This study aims to determine the effect of the Hanging Ball Training Model on the Service Ability of Female Volleyball Extracurricular at SMPN 2 Bengkulu City. This study refers to a quantitative research approach and uses quasi-experimental research techniques. The sample in this study were 30 students. The sampling technique used was Purposive sampling technique. The nstrument used was top service test. Based on the results of the study that showed there was a significant effect between hanging ball training on service ability on volleyball at SMPN 2 Bengkulu City, it was proven from t_count = 5.397 > t_table = 2,048 at a significant level = 0.05. with an increase in the percentage of 30.06%, then Ha is accepted. "There is an effect of Hanging Ball training on the Service Ability of Extracurricular Female's Volleyball at SMP 2 Bengkulu City" is accepted. Keywords: Hanging Ball, Volleyball, Extracurricular